2021
DOI: 10.2147/dmso.s302761
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Visceral Adiposity Index and Lipid Accumulation Index for Microalbuminuria in Newly Diagnosed Type 2 Diabetes Patients

Abstract: This study aims to investigate the predictive value of visceral adiposity index (VAI) and lipid accumulation index (LAP) for microalbuminuria (MAU) in patients with newly diagnosed Type 2 diabetes (T2DM). Patients and Methods: This study included 335 patients with newly diagnosed T2DM patients from Hebei General Hospital. All the patients aged from 18 to 65 years old include 226 males and 109 females. Patients information and blood indicators were Collected and calculated the LAP and VAI scores. All the patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Our study identified VAI, TyG and LAP as sensitive predictors of hypogonadism in men with type 2 diabetes, therefore suggesting their routine use to direct the patient to andrological evaluation. Previous studies in males with type 2 diabetes or metabolic syndrome showed that higher values of one or more of these three indices express worst anthropometric parameters, poorer glyco-metabolic control, and elevated cardiometabolic risk and more diabetic vascular complications [ 18 , 34 37 ]. In addition, TyG and LAP have been observed as predictors of hypogonadism in middle-elderly male general Chinese population [ 22 , 23 ], and VAI as a marker of cardiometabolic risk in men with congenital hypogonadotropic hypogonadism [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study identified VAI, TyG and LAP as sensitive predictors of hypogonadism in men with type 2 diabetes, therefore suggesting their routine use to direct the patient to andrological evaluation. Previous studies in males with type 2 diabetes or metabolic syndrome showed that higher values of one or more of these three indices express worst anthropometric parameters, poorer glyco-metabolic control, and elevated cardiometabolic risk and more diabetic vascular complications [ 18 , 34 37 ]. In addition, TyG and LAP have been observed as predictors of hypogonadism in middle-elderly male general Chinese population [ 22 , 23 ], and VAI as a marker of cardiometabolic risk in men with congenital hypogonadotropic hypogonadism [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…WHR was defined as WC [cm] /HC [cm]. Visceral adiposity index (VAI) was calculated according to Qi et al 17 …”
Section: Methodsmentioning
confidence: 99%
“…Weight loss can reverse to some extent the underlying metabolic abnormalities caused by type 2 diabetes, resulting in better glycemic control ( 28 ). Moreover, LAP is also relevant to diabetic complications such as diabetic nephropathy, diabetic retinopathy, and cardiovascular risk ( 29 31 ). Considering the high prevalence rate, serious complications, and serious social and economic burden caused by type 2 diabetes, it is very important to find a low-cost, easy-to-operate, and easy-to-calculate indicator to identify diabetes as early as possible and conduct lifestyle or drug intervention if necessary.…”
Section: Discussionmentioning
confidence: 99%